MarTech Collaboration: The Role of Marketing Technology, Local Culture, and Social Networks in Enhancing Business Performance in the Digital Era - Ahmad Syaiful Affa; Meliza; Afrinar Pramitasari (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
The advancement of digital technology, particularly MarTech (Marketing Technology), has transformed business paradigms. However, the success of MarTech requires integration with local culture and social networks to achieve sustainable business performance. This study aims to explore the collaboration of MarTech, local culture, and social networks as a strategy for business growth. The research employs a mixed-method approach, combining qualitative and quantitative analyses in parallel. Qualitative data were obtained through literature analysis, while quantitative data measured business performance through visibility, engagement, and sales metrics. The findings indicate significant improvements in business performance during the March-May 2024 period, with a Return on Ad Spend (ROAS) reaching 10.5 in April. However, the conversion rate from Add to Cart (ATC) to purchase remains low, ranging from 8.6% to 19.7%. These findings highlight the need for retargeting optimization, enhanced user experience, and targeted promotional strategies. In conclusion, the integration of MarTech, local culture, and social networks can improve business performance, but further evaluation is required to enhance conversion rates and campaign effectiveness. This study provides strategic guidance for businesses to leverage technology and local culture for sustainable growth.